Dietary Zinc Intake Affects the Association Between Dietary Vitamin A and Depression: A Cross-Sectional Study - Hu, Biao; Lin, Zheng-yang; Zou, Run-pu; Gan, Yin-wen; Ji, Jia-ming; Guo, Jing-xi; Li, Wan-gen; Guo, Yong-jing; Xu, Hao-qin; Sun, Dong-lin; Yi, Min (Frontiers in Nutrition, 2022)
Abstract Introduction: Circulating vitamin A concentrations correlate with depression. Zinc has been reported to be associated with lower depression. In addition, zinc is an important cofactor in the activation of vitamin A. However, there are no experimental studies examining the effect of dietary zinc intake on the relationship between dietary vitamin A and depression. Materials and Methods: The data for this study came from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 and involved 70,190 participants. By stratifying participants into intake categories based on zinc (low zinc intake <9.71 mg/day; high zinc intake: ≥9.71 mg/day). We further assessed the difference between vitamin A and depression in participants with low and high zinc intake (interaction test) using univariate logistic regression of intake participants. Result: In this cross-sectional study, the association between dietary vitamin A and depression was associated with higher or lower zinc intake (OR: 0.91, 95% CI: 0.84-0.99 versus OR: 1.07, 95% CI: 0.99-1.17). In addition, there was evidence that the interaction between vitamin A levels and zinc intake reduced depression (p-value = 0.001). Conclusion: Our findings suggest that zinc intake may influence the relationship between dietary vitamin A and depression. Of course, our findings require further randomized controlled trials to enhance the credibility